Impact of the no-touch harvesting technique on the vessel diameter of saphenous vein grafts for coronary artery bypass graftingCentral MessagePerspective - Hiroshi Kurazumi, MD, PhD; Ryo Suzuki, MD, PhD; Ryosuke Nawata, MD; Toshiki Yokoyama, MD; Sarii Tsubone, MD; Akihito Mikamo, MD, PhD; Kimikazu Hamano, MD, PhD (JTCVS Techniques)
Objectives: To explore the impact of the no-touch harvesting technique on the vessel diameter of saphenous vein grafts. Methods: This retrospective, single-center study enrolled 166 patients who underwent isolated coronary artery bypass grafting using saphenous vein grafts. Saphenous vein grafts were harvested conventionally in 83 patients (conventional group) and using the no-touch technique in 83 patients (no-touch group). We analyzed graft patency and the vessel diameters of saphenous vein grafts in the pre- and postoperative states. The diameter mismatch between the saphenous vein grafts and the coronary artery at the anastomotic site was also measured; preoperative diameter was measured using ultrasound imaging, and the postoperative diameter was measured using electrocardiogram-gated enhanced computed tomography. Results: A total of 135 saphenous vein grafts (66 and 69 grafts in the conventional and no-touch groups, respectively) were evaluated for postoperative patency. Graft patency was equivalent in the 2 groups (conventional, 96.9% vs no-touch, 100%; P = .24). A detailed evaluation was performed in 109 saphenous vein grafts (52 and 57 grafts in the conventional and no-touch groups, respectively). Saphenous vein graft diameter was significantly distended in the conventional group (preoperative, 2.6 ± 0.7 mm vs postoperative, 3.4 ± 0.5 mm; P < .0001). However, saphenous vein graft diameter did not change in the no-touch group (preoperative, 2.9 ± 0.4 mm vs postoperative 2.8 ± 0.4 mm, P = .33). The diameter mismatch was significantly smaller in the no-touch group (conventional 1.4 ± 0.6 mm vs no-touch 1.0 ± 0.4 mm, P < .0001). Conclusions: The no-touch technique avoids the expansion of graft diameter and diameter mismatch between the saphenous vein grafts and coronary artery.